Pemurnian Gliserol dari Hasil Samping Produksi Biodiesel Minyak Kelapa Sawit (Purification of Glycerol from the By-Product of Palm Oil Biodiesel Production) - Fahrizal Hazra; Irfan Septiawan (IPB University, 2014)
The process of making biodiesel made of palm oil produced as a by-product of glycerol with low purity levels, liquids, viscous blackish brown with a very alkaline pH (pH >10). Glycerol is often referred to as crude glycerol. The process of refining glycerol that is by adding phosphoric acid concentration range. The average value of the levels of glycerol from glycerol purification results on the phosphoric acid concentration of 2.5%, 5% and 7.5% (v/v) i.e. 81.2205%, 83.4609% and 80.7595%. Determination of the levels of glycerol results showed samples of glycerol rough after the addition of phosphoric acid with different concentrations of already existing standards. The result analysis of glycerol after purification by the addition of phosphoric acid at concentrations of 5% is most suitable for the process of improving the purity of glycerol.Keywords: crude glycerol, purification, phosphate acid, glycerol content